1985
DOI: 10.1111/j.1399-3054.1985.tb02822.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light and benzyladenine on dark‐treated growing rice leaves (Oryza sativa). I. Changes in chlorophyll content and catalase activity

Abstract: 1985. Effect of light and benzyladenine on dark-treated growing rice leaves (Oryza saiivti). I. Changes in chlorophyll content and catalase activity. -Physiol. Plant. 63: 79-86.Light-and benzyladeuine-indiiced reversal of the changes in chlorophyll content and catalase activity were studied in the attached first leaf of Oryza sativa L. cv. Bala, kept in darkness for different periods before maturation. Dark treatment caused a decrease in chlorophyll content and catalase activity at all times. Light treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…This concurs similar findings reported in detached rice leaves (Kar and Mishra, 1976;Patra et al, 1979;Reddy et al, 1985), tobacco (Parish, 1968) and oat (Birecka et al, 1979;Kar and Feieraband, 1984). There are also reports of suppression of peroxidase activity by growth regulators in barley leaves (Sharma and Biswal, 1976) and pea stem sections (Henry and Jordan, 1977).…”
Section: Changes In Peroxidase Activitysupporting
confidence: 77%
See 1 more Smart Citation
“…This concurs similar findings reported in detached rice leaves (Kar and Mishra, 1976;Patra et al, 1979;Reddy et al, 1985), tobacco (Parish, 1968) and oat (Birecka et al, 1979;Kar and Feieraband, 1984). There are also reports of suppression of peroxidase activity by growth regulators in barley leaves (Sharma and Biswal, 1976) and pea stem sections (Henry and Jordan, 1977).…”
Section: Changes In Peroxidase Activitysupporting
confidence: 77%
“…The information so far available indicated that the excised senescencing leaves incubated in dark exhibited a decreased catalase activity in rice leaves (Kar and Mishra, 1976;Patro et al, 1978), ragi leaves (Reddy et al, 1985). Anagalli leaves (Trippi et al, 1980 …”
Section: Changes In Catalase Activitymentioning
confidence: 99%
“…The assay principle was based on catalase's reaction to breakdown H 2 O 2 , which absorbs maximum at 405 nm. Spectrophotometrically, the POD activity was determined at (Reddy et al, 1985). Purpurogallin, which has a wavelength of 420 nm, is produced in the assay by the reaction of peroxidase and pyrogallol.…”
Section: Estimation Of the Antioxidant Enzymes Activitiesmentioning
confidence: 99%